Impact of Global Health Scholarship Programs in the Faculty of Medicine at Mbarara University of Science and Technology - Tusiimire, Jonans; Nakiwala, Miriam Josephine; Turigye, Brian; Ansiimire, Daphine; Kembabazi, Annet; Asiimwe, Stephen; Ngonzi, Joseph (International Medical Education, 2024)
In recognition of the critical role of residency programs in narrowing health care inequalities, Global Health scholarships were introduced at Mbarara University of Science and Technology (MUST) in 2011. Since then, at least 154 postgraduate students in priority programs have benefited. We conducted an online cross-sectional survey to examine how the scholarships and beneficiaries have impacted MUST and the community. Fifty (50) beneficiaries, representing 32.5%, responded, of whom 36 (72%) were alumni. Most respondents were males (n=30;60%) pursing Master of Medicine (n=29;58%) or Master of Nursing Science (n=20;40%) programs. The scholarship schemes included First Mile (n=29;58%), Kayanja (n= 12; 24%), Paiko (n= 5; 10%) and Seed (n= 4; 8%). The majority of the scholarships supported both tuition and research fees (n=41;82%), therest being partial. Career advancement was undertaken by eight (16%) of the scholars in the form of fellowships (n=3;6%), other masters (n=3;6%) and PhDs (n=3;6%), with some students having attained a combination of these. All scholars belonged to at least one health professional association. Over 88%(n=32) of the alumni and 28%(n=4) of the students were employed. The majority of those employed were in the public sector (n=24;66.7%), mainly the health sector (n=18; 50%), academia (n=14; 38.9) or both (n=4; 11.1%). There was a high impact on health care provision, undergraduate training and research carried out by the scholars both during training and post-graduation. High levels of career satisfaction, scholarship impact and academic program relevance were reported. The findings provide insights on how low-fund specialty scholarships can have a far-reaching impact on local training, healthcare and research in low-and middle-income countries.
Keywords: Alumni; Satisfaction; Tracerstudy; Scholarship; Global health collaborative; Medical education